The Crisis of the European Union: An Application of Murphy’s Law - Adins Vanbiervliet, Sebastien (2017)
The present article suggests that the various crises that have been affecting the European Union since 2008 have essentially structural causes. Two of them are the subject of this analysis. On the one hand, European regionalism is experiencing a crisis of legitimacy due to its technocratic character, the predominance of the neoliberal paradigm in its policies and the lack of a properly European identity among the population. On the other hand, the EU faces a crisis of a geopolitical kind that includes three main components: the growing vulnerability towards the MENA; the reappearance of a «Cold War logic» in its relations with Moscow and, in general, the same characteristics of the current international order.